DIGITAL LITERACIES AND INTERACTIVE MULTIMEDIA-ENHANCED TOOLS FOR LANGUAGE TEACHING AND LEARNING - Hülya Mısır (Informascope, 2018)
The primary aim of the paper is to introduce digital literacies and the utilization of interactive and multimedia-enhancedtools for language learning purposes in and out of institutional settings. The topics covered in this paper include what digital literacy means in language education contexts and utilization of social media, online gaming, tagging, picture, voice, and video editing tools, mixing tools, interactive HTML5 contents, translation tools, search engines and (visual) thesauruses to evaluate, contribute, and create the information rather than being a mere consumer. Bearing in mind the nature of interaction and collaboration of the digital tools, suggested ways to integrate these tools to teaching and learning of languages are also presented. The paper also identifies common concerns and challenges in regard to motivation to use digital tools, judging the validity of a source, prohibitions due to country policies, plagiarism, filtering in search engines, and insensitivity with online language, which hinders the effective use of digital tools.